SOCIETAL THREADS IN LITERATURE: AN ANALYSIS OF CHARACTER DYNAMICS IN HAMKA’S TENGGELAMNYA KAPAL VAN DER WIJCK - Ramadani, Yasinta Sahla; Nurholis, Nurholis (Saksama: Jurnal Sastra, 2023)
In this study, we adopt a sociological lens to analyze characterizations in Tenggelamnya Kapal Van Der Wijck. We explore the social and contextual factors influencing these characters, aiming to illuminate the complex network of relationships, power structures, and gender roles within the novel. This analysis seeks to enhance our comprehension of the societal and cultural context of the characters and their alignment with wider social realitiesThe study’s findings reveal a strong correlation between the novel’s characterizations, the socio-cultural and historical context of the Minangkabau people during the period in question. Zainuddin, the novel’s protagonist, grapples with the challenge of preserving his identity as a Minang individual of lower social standing. The characterizations of other figures, such as Hayati and Aziz, play a pivotal role in shaping Zainuddin’s life trajectory.This research enriches the field of literary studies by integrating sociological elements into the analysis of character development in a literary piece. The implications of this study include fostering a more profound comprehension of sociology’s role in shaping characters in literature, and generating novel insights into the historical Minangkabau society.